Identification and differentiation of Candida species using specific polymerase chain reaction (PCR) amplification of the phospholipase B gene - Harmal, Nabil S.; Khodavandi, Alireza; Alshawsh, Mohammed A.; Jamal, Farida Fatema @ Farida; Sekawi, Zamberi; Ng, Kee Peng; Chong, Pei Pei (Academic Journals, 2013)
Candida species are the major cause of mortality in both immunocompromised and critically ill patients. Therefore, the early diagnosis and differentiation of Candida species isolated from clinical samples is principally important due to their inherently variable antifungal resistance pattern. Herein, rapid and species-specific polymerase chain reaction (PCR)-based molecular method was developed for the identification of the four species of Candida most commonly isolated from clinical specimens, namely Candida albicans, Candida parapsilosis, Candida glabrata and Candida tropicalis. The developed method targeted the phospholipase B gene (PLB) as a novel target. We determined the sequences of this gene in previous work. The primers designed achieved highly specific identification of the selected species using simplex PCR assay, which were confirmed by sequencing. There was no cross-amplification of other Candida species nor other fungal organisms tested. The simplex PCR assay yielded detection limits of 1 to 10 cells/ml and 10 fg/µl DNA. These results showed that the PLB gene provides a novel target that could be used for the identification and detection of medically important Candida species from the clinical samples.